Gerakan Remaja Bugar melalui Pelatihan Senam Penjas-UNG 22 di SMA Negeri 1 Telaga - Ella H Tumaloto; Suriyadi Datau; Ruslan Ruslan; Sarjan Mile (-, 2026)
The low level of physical activity among secondary school adolescents has become one of the contributing factors to declining physical fitness, increasing sedentary behavior, and limited awareness of the importance of a healthy lifestyle. Preliminary observations indicate that school gymnastics activities remain monotonous, lack innovative instructional models, and are not implemented consistently. These conditions have reduced students' motivation to participate in regular physical activity. Therefore, a community service program was designed through the Penjas-UNG 22 Gymnastics training as an innovative, easy-to-learn, engaging, and age-appropriate exercise model for secondary school students. This community service initiative aims to enhance students' knowledge, practical skills, and active participation, while strengthening the competencies of Physical Education, Sports, and Health (PJOK) teachers in implementing Penjas-UNG 22 Gymnastics as a sustainable school-based healthy lifestyle program. The implementation methods included partner needs assessment, program socialization, theoretical and practical training on Penjas-UNG 22 Gymnastics, implementation mentoring, monitoring, and evaluation. Program effectiveness was evaluated through pre- and post-tests of participants' knowledge, observation of movement skills, and assessment of participation levels throughout the activities. The expected outcomes include improved competencies of teachers and students in performing Penjas-UNG 22 Gymnastics, the development of a school gymnastics implementation guide, the establishment of a routine gymnastics program as part of a healthy school culture, publication of scientific articles in community service journals, dissemination through mass media, production of activity documentation videos, and strengthened collaboration between the Gorontalo State University and partner schools. The program is expected to contribute to improving adolescents' physical fitness, fostering discipline, teamwork, and responsibility, while promoting a sustainable culture of active and healthy living within the school environment.